Pelatihan Manejemen Komunikasi Merek Kepada Pelaku Usaha dalam Mendukung City Branding Cirebon - Suharyanti, Suharyanti; Hanathasia, Mirana; Fortunisa , Ananda (Indonesian Journal for Social Responsibility, 2019)
In 2917 Indonesian Government has tergetted 8 millions small-medium enterprises (SME) to go online at 2019. Some digital workshops have been conducting to SME all over Indonesia, includes in Cirebon. Now, there are 1698 SME in Cirebon. At the beginning, lot of products from Cirebon showed the uniqueness of Cirebon as Shrimp City such as shrimp cracker, shrimp paste, batik linen and glass painting. But now, many SME develop new products which may be the new identifying mark for Cirebon in the future. They are fried onion, steel relief, soap, etc. However, a lot of small-medium enterprises do not able to create marketing communication strategy. Therefore to develop the businsess of small-medium enterprise, it is necessary to conduct a workshop on brand communication management with subject of creating an attractive theme to be communicated in product packaging or promotion media and subject of preparing media plan strategy to promote products. By implementing the effective brand communication, it not only communicates the brand itself, but also it is part of supporting Cirebon city branding.